Beyond the Horizon Broadening Our Understanding of OER Efficacy - Schilling, Kaitlin (Open textbook library., 2023)
Beyond the Horizon: Broadening Our Understanding of OER Efficacy is a concise yet comprehensive resource designed to provide insight into the current state of research and reporting on Open Educational Resources (OER) efficacy. This guide explores existing frameworks, delves into key themes and gaps, and highlights emerging opportunities in the realm of OER efficacy.